Interpretation of CT (Computed Tomography) Scan for Covid- 19 (OMICRON) - Antesar Rheem Obead, Aminah Kadhum Murad, Mohend A.N. Al-Shalah, (Pakistan Journal of Medical & Health Sciences, 2022)
COVID-19 is a virus that can cause disease. Phylogenetic analysis Bats have been discovered to have a full genome sequence, according to research done with available entire genome sequences. The COVID-19 virus reservoir has been identified, however the intermediate host(s) has yet to be identified. now. This study was conducted in Marjan Teaching Hospital in Babylon for all patients infected with Covid 19 disease during January of 2022 and their ages were between 30-55, where the diagnosis was made by CT-scan. the reports that I will mention that the new mutation from Corona does not cause severe damage to the lung, and the infection rate is less than 45% in the lung. She also indicated that all patients were exposed to severe diarrhea without losing the sense of smell and taste. From this, we conclude that the new mutations in Covid -19 are Less severe and less severe, and the vaccine reduces a high rate of infection, as most of the vaccinated people had a very weak rate. And here are pictures of the reports of the new mutant from Covid -19 (OMICRON).